A first-principles study of the avalanche pressure of alpha zirconium. Issue 76 (1st August 2016) - Peng, Qing; Ji, Wei; Lian, Jie; Gao, Fei; Peng, Shuming; Huang, Hanchen; De, Suvranu
Abstract : The critical swelling pressure, the avalanche pressure, is P a  = −15 GPa for alpha zirconium. Abstract : We investigate the stability of a monovacancy in alpha zirconium under various strains and pressures by examining the vacancy formation energy through first-principles calculations. There is a maximum formation energy of 2.35 eV under uniaxial strain corresponding to a c / a ratio of 1.75. Under volumetric strain, the formation energy increases as the strain increases. The formation energy as a function of the volumetric stress or pressure was also examined, with a minimum value of 2.00 eV at zero pressure. Using the equations of state method, we find that the formation volume of the vacancies decreases as the pressure increases, with a value of 0.6 unit-atom-volume at zero pressure. The formation enthalpy increases monotonically as the pressure increases. We predict that the avalanche pressure of alpha zirconium is −15 GPa, where vacancy formation is exothermic, causing avalanche swelling and the failure of the material.